2019
DOI: 10.25095/mufad.606020
|View full text |Cite
|
Sign up to set email alerts
|

Borsa İstanbul’da İşlem Gören Turizm Şirketlerinin Nakit Akış Profillerinin İncelenmesi

Abstract: The aim of the study is to analyze the cash flow profiles of tourism companies that are traded at the XTRZM index of Borsa Istanbul (BIST) by benefiting from the cash flow patterns method. The analysis covers quarterly periods from 2012 to 2016 consisting of 600 firm-year observations. Findings indicate that the tourism companies at Borsa Istanbul are in their maturity and growth phases. Their cash flow profiles are identified as Pattern 2: Successful business, Pattern 4: Growing business and Pattern 6: Fast g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…In the study conducted by Kablan and Güvemli (2019), the cash flow profiles of the tourism companies included in the BIST XTRZM index were examined using Cash Flow Patterns Method for the years 2012-2016. They reported that the enterprises had the profiles of Model 4 "Growing Business", Model 6 "Fast Growing Young Business", and Model 2 "Successful Business".…”
Section: Literature On Researchmentioning
confidence: 99%
“…In the study conducted by Kablan and Güvemli (2019), the cash flow profiles of the tourism companies included in the BIST XTRZM index were examined using Cash Flow Patterns Method for the years 2012-2016. They reported that the enterprises had the profiles of Model 4 "Growing Business", Model 6 "Fast Growing Young Business", and Model 2 "Successful Business".…”
Section: Literature On Researchmentioning
confidence: 99%